2019
DOI: 10.1088/1755-1315/374/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO-mediated oxidation cellulose pulp modified with Monosodium Glutamate (MSG)

Abstract: Monosodium glutamate (MSG) was conjugated onto cellulose microfibrils (CMF) by the reaction in acetone solvent at the presence of triethylamine and paratoluene sulfonyl chloride. Results showed that the thermal decomposition of CMF-MSG slightly decreased to lower temperature decomposition confirmed by thermogravimetry analysis (TGA) after MSG was present on CMF surfaces which was confirmed by the reduction of intensity in carboxyl groups bands under infra-red spectroscopy (FTIR) observation. After drying, CMF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…As a result, the surface of the hydrogel beads displayed a granulated structure (Figure 5(c)). This observation indicated that the pores were now filled with dye, which was in good accordance with the findings reported in the literature for similar works [27,29].…”
Section: Morphology Of Biocomposite Beadssupporting
confidence: 93%
See 2 more Smart Citations
“…As a result, the surface of the hydrogel beads displayed a granulated structure (Figure 5(c)). This observation indicated that the pores were now filled with dye, which was in good accordance with the findings reported in the literature for similar works [27,29].…”
Section: Morphology Of Biocomposite Beadssupporting
confidence: 93%
“…Sodium alginate, CaCl2, polyethyleneimine (PEI) with an average MW of ~270.000 and Congo Red were purchased from Sigma Aldrich. The TEMPOoxidized cellulose nanofibrils were prepared according to our previous work [28,29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the thermal degradation of pure cellulose is around 345 • C, for the TEMPOoxidized cellulose and the cellulose nanofiber, it happened at 245 • C. This significant decrease can be due to lower thermal degradation of carboxylate anions (COO-) on the C6 carbon of cellulose chain [34,55]. It can also be claimed that the reduction in cellulose crystallinity, resulting from its oxidation, is another contributing factor to the decrease in degradation temperature, as corroborated by the Crystallinity index (CrI) in the XRD analysis [56].…”
Section: Thermal Properties Of Nanofibers (Tga)mentioning
confidence: 99%
“…Moreover, TOCNF aqueous dispersions can switch reversibly from an elastic-to a viscousdominated regime, a behaviour typical of thixotropic materials (Mendoza et al 2018). Furthermore, the gelation process of TOCNF aqueous dispersions can be improved and tuned by varying different conditions, like pH (Saito et al 2011), temperature, surfactants (Crawford et al 2012;Quennouz et al 2016), and electrolytes (Dong et al 2013;Fukuzumi et al 2014;Masruchin et al 2019;Fiorati et al 2020) concentration. Among all these approaches, the addition of polyvalent electrolytes (e.g.…”
mentioning
confidence: 99%